2006
DOI: 10.1073/pnas.0507198103
|View full text |Cite
|
Sign up to set email alerts
|

In situ labeling of immune cells with iron oxide particles: An approach to detect organ rejection by cellular MRI

Abstract: In vivo cell tracking by MRI can provide means to observe biological processes and monitor cell therapy directly. Immune cells, e.g., macrophages, play crucial roles in many pathophysiological processes, including organ rejection, inflammation, autoimmune diseases, cancer, atherosclerotic plaque formation, numerous neurological disorders, etc. The current gold standard for diagnosing and staging rejection after organ transplantation is biopsy, which is not only invasive, but also prone to sampling errors. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
231
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(240 citation statements)
references
References 40 publications
9
231
0
Order By: Relevance
“…Furthermore, the niche environment that the stem cells exist in can be preserved. More interestingly, the distribution of cells in the olfactory bulb in response to different odor stimulations, or the ability to cause migratory deviations from the RMS in response to injury, should be amenable to study using these techniques, possibly to the point of detecting single cells (Shapiro et al, 2006;Wu et al, 2006;Heyn et al, 2006). The migratory pathway and endpoints can be readily co-registered with a wide variety of other anatomical and functional information available from MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the niche environment that the stem cells exist in can be preserved. More interestingly, the distribution of cells in the olfactory bulb in response to different odor stimulations, or the ability to cause migratory deviations from the RMS in response to injury, should be amenable to study using these techniques, possibly to the point of detecting single cells (Shapiro et al, 2006;Wu et al, 2006;Heyn et al, 2006). The migratory pathway and endpoints can be readily co-registered with a wide variety of other anatomical and functional information available from MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Second, our model assumes that the average contrast over a region of interest is comprised of numerous voxels. However, when certain cellular CAs, such as micron-sized SPIO agents (5,22), are used, in vivo contrast may be highly localized and punctate. This may offer improved detectability, and the contrast model may underestimate contrast in these cases.…”
Section: Discussionmentioning
confidence: 99%
“…SPIO particles with surfaces conjugated to targeting entities, such as peptides or antibodies, have also been described (4). Intracellular applications of SPIO for cell-tracking in animal models is a rapidly evolving research area (5), and the clinical translation of these techniques is already in the early stage (6).…”
mentioning
confidence: 99%
“…Thus, it serves as an effective cellular system for innate immune response evaluation. Recent reports mainly focused on labeling monocyte cells with NPs for therapeutic imaging (Settles, et al, 2011;Von zur Muhlen et al, 2010;Wu et al, 2006), and only a few reports demonstrated the proinflammatory effects of iron oxide NPs on human monocyte cell lines (Laskar et al, 2012;Zhu et al, 2011). Further understanding of the interactions between NPs and human monocyte cell line will be beneficial for predicting NP-induced inflammatory responses, and provide valuable information for NP design to achieve alleviated inflammation in biological systems.…”
Section: Introductionmentioning
confidence: 99%